Transformation of South Africa's energy landscape: Policy implications, opportunities, and technological innovations in the Fourth Industrial Revolution - Kingsley Ukoba; Tien-Chien Jen; Abdulfatah Abdu Yusuf (Energy Strategy Reviews)
South Africa's energy sector is undergoing a critical transformation amid challenges of accessibility, environmental sustainability, and modernization. This study critically examines the nation's energy landscape, focusing on policy implications, renewable energy adoption, and Fourth Industrial Revolution (4IR) technologies reshaping the sector. A systematic review was conducted, analyzing over 500 peer-reviewed publications, government reports, and industry data. From these sources, more than 200 were selected based on their relevance and empirical data. The review aimed to identify trends, research gaps, and evidence supporting the transition to sustainable energy solutions. Findings reveal a heavy reliance on coal, accounting for 77 % of electricity generation, while renewable energy contributes only 12 %. In 2021, South Africa generated 245,000 GWh of electricity, but coal-fired power plants remain significant sources of carbon dioxide, sulfur dioxide, and mercury emissions, underscoring the urgency of transitioning to cleaner energy. The Renewable Energy Independent Power Producer Procurement Programme (REIPPPP) has attracted over $20 billion in investments, aiming to integrate 17.8 GW of renewable energy by 2030. Current capacities include 2500 MW of solar PV and 3670 MW of wind energy, with projections targeting 40 % renewable energy by 2030, guided by the Integrated Resource Plan (IRP). Despite progress, rural electrification disparities persist, necessitating inclusive energy solutions. Key recommendations include strengthening regulatory frameworks to accelerate renewable energy adoption, addressing energy poverty through decentralized systems, and fostering public-private partnerships for infrastructure development. 4IR technologies, such as smart grids and decentralized energy systems, offer transformative pathways for achieving sustainable energy goals. These strategic interventions are essential for reducing carbon emissions and ensuring an inclusive, sustainable energy future for South Africa.